Perbedaan Karakter Atlet Tim dan Atlet Individu - Muhammad Syahida Rizqy; Fajar Kurniawan (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. This study aims to identify differences in the psychological characteristics of athletes participating in team sports and individual sports, specifically students of the Jadimulya Badminton Coach and the Putra Bisma Football School. Using a qualitative descriptive approach, the research involved athletes from both institutions as subjects. Human beings functioned as the main research instrument, supported by observation and interview guidelines used to explore psychological traits relevant to each sport context. Material and methods. The results show that clear psychological differences exist between team and individual athletes. Team athletes, such as football players, rely heavily on cooperative abilities, effective communication, and collective motivation to achieve shared goals. They must navigate team dynamics, manage interpersonal relationships, resolve conflicts, and maintain team cohesion to ensure optimal performance. Leadership, adaptability, and the ability to function within a structured social environment emerge as essential characteristics. In contrast, individual athletes such as badminton players demonstrate stronger independence, personal motivation, and self-regulation. Their success depends largely on individual skill mastery, consistency, and mental resilience under pressure. Individual athletes develop personal strategies, emphasize innovation in technique, and are required to manage competitive stress without relying on teammates. Creativity in badminton is rooted in technical execution, while creativity in football tends to emerge through collective strategy and team formations. Result. The findings also highlight distinct character tendencies: badminton athletes show a high level of autonomy and focus on personal performance refinement, whereas football athletes depend on teamwork, coordination, and group synergy. Conclusion. significant psychological differences distinguish team athletes from individual athletes. Team-sport athletes require communication skills, collective motivation, and the ability to adapt within team dynamics, while individual-sport athletes prioritize independence, mental endurance, self-motivation, and autonomous skill development.